Paroxysmal symptoms as the first manifestations of multiple sclerosis. - Twomey, J A (1980)
Paroxysmal symptoms are described in 14 patients with undoubted or suspected multiple sclerosis (MS). In seven of the patients the paroxysms were the first symptom of the disease, although only one has developed definite MS so far. The clinical features have been compared with 153 patients previously reported in the literature which has been reviewed, with special reference to 36 in whom paroxysmal symptoms were the initial manifestations of MS. Attention has been focused on paroxysmal symptoms of brain stem and spinal cord origin of the following types: paroxysmal dysarthria and ataxia, diplopia, tonic seizures, paroxysmal akinesia, paroxysmal sensory disturbances and pains. Examples of each type have been reported as the first symptoms of MS with remissions ranging from less than one to 21 years before other manifestations of MS have developed.